2012
DOI: 10.1134/s0965545x12020010
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes in blends of linear polymers during their physical aging

Abstract: 125Aging of polymers is a combination of physical and chemical processes occurring during storage, process ing, and exploitation of polymeric materials and resulting in a change in their properties [1]. Depend ing on which processes prevail, chemical and physical aging of polymers can be distinguished. Under the action of oxygen, ozone, high temperature, light, pen etrating radiation, mechanical stress, etc., degradation processes may occur in polymers; they entail decom position of polymer chains and lead to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Thermal analysis includes thermogravimetric analysis (TG), differential scanning calorimetry (DSC), dynamic thermomechanical analysis (DMA), and so on, which are relatively mature. [4][5][6] However, thermal analysis involves the physical and chemical parameters of the sample at different temperatures, which is a destructive test of the sample not allowed in the industry field. Infrared spectroscopy, ultraviolet spectroscopy, and Raman spectroscopy are the representative methods that work nondestructively by detecting carbonyl groups, conjugated structures, and energy level transitions to determine the degree of material aging, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal analysis includes thermogravimetric analysis (TG), differential scanning calorimetry (DSC), dynamic thermomechanical analysis (DMA), and so on, which are relatively mature. [4][5][6] However, thermal analysis involves the physical and chemical parameters of the sample at different temperatures, which is a destructive test of the sample not allowed in the industry field. Infrared spectroscopy, ultraviolet spectroscopy, and Raman spectroscopy are the representative methods that work nondestructively by detecting carbonyl groups, conjugated structures, and energy level transitions to determine the degree of material aging, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The observation of the color, hardness, and gloss of the material is an experience‐based method in the field, which is an inaccurate qualitative judgment. Thermal analysis includes thermogravimetric analysis (TG), differential scanning calorimetry (DSC), dynamic thermomechanical analysis (DMA), and so on, which are relatively mature 4–6 . However, thermal analysis involves the physical and chemical parameters of the sample at different temperatures, which is a destructive test of the sample not allowed in the industry field.…”
Section: Introductionmentioning
confidence: 99%
“…[1] This phenomenon, which is thermo-reversible, affects several physical properties such as density, impact strength, permeability, modulus, specific enthalpy, and so forth. [1][2][3][4][5] This is valid for polymers, [6][7][8][9][10][11][12][13][14] polymer blends, [15][16][17][18][19][20] and polymer nanocomposites. [21][22][23] It is thus highly important to study the physical aging of polymer systems to determine their long-term evolution.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11]13,14] The most recent works focused on studying the effect of aging over blends miscibility. [16][17][18][19][20] Chang et al [19] performed stress relaxation measurements to compare the effect on neat PS with its blend with poly(p-phenylene oxide) PS:PPO and poly(vinyl methyl ether) (PS:PVME). The results showed that the stress relaxation time of the blends decreased, indicating higher free volume content compared to PS alone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation